SUSTAINABLE MANUFACTURING PRACTICES AND ENVIRONMENTAL PERFORMANCE OF TABLE WATER COMPANIES (Journal of Technology and Operations Management, 2022)
The study examined how sustainable environmental performance is impacted by sustainable manufacturing practices in table water companies duly registered by National Agency for Food and Drug Administration and Control (NAFDAC). A random sample of 297 table water companies was used for the investigation out of which 247 were validly completed. Using the Mahalanobis distance approach, three responses demonstrated the presence of outliers which were deleted from the dataset.  Therefore, 244 responses were used for the study.  Multiple regression analysis was used to establish the statistical significance and relationship between sustainable manufacturing practices and environmental performance of the selected table water companies. The study found that the investigated sustainable manufacturing practices (sustainable product development, sustainable packaging, and sustainable waste management) have a positive and significant impact on the environmental performance of table water companies. The study recommends that table water companies should invest more resources in state-of-the-art production technologies that could enhance manufacturing process and reduce energy consumption.